An overview on islamic principles of religious diversity at workplaces in Malaysia - Nik Mahmod, Nik Ahmad Kamal; Mohd Yusoff, Rahmawati; Mohd, Azizah; Mohd Noor, Noor Azlan; Harun, Azmi; Che Mohd Salleh, Marhanum; Baharudin, Mohammad Hidir (Department of Syariah Judiciary Malaysia & Ahmad Ibrahim Kulliyyah of Laws, IIUM, 2021)
The liberty of workers to exercise their religion and beliefs is one of the rights of workers at their workplace. Nonetheless, there is not much discussion on this issue, particularly in situations where there are close interactions between Muslims and non-Muslims at the workplace. This research examines the principles and attitudes as shown by the Prophet (PBUH) in interacting with non-Muslims. This discussion is necessary so that any constraints to practice one’s religion such as limitations as to the facilities and opportunities to perform the rites can be removed. This chapter is based on a research that takes a doctrinal approach where the issue will be examined from the perspective of the Qur’an and the Sunnah as the primary sources of Islamic law. The research output includes increasing references and guidelines regarding Islamic principles on religious diversity, in terms of dealing with the non-Muslims so that everyone will have the opportunity to practice their religious duties at work.